Percepción y temporalidad: Husserl frente a Heidegger - García, José Luis (2024)
This contribution is part of a copious bibliographic tradition that has sought the points of encounter and disencounter between the two most relevant phenomenologists of the 20th century: Husserl and Heidegger. Starting from the critical foundations of the 1919 public emergence of Heidegger’s project of an originary science, I propose, first of all, to review his criticism of the history of philosophy, which, in his opinion, has committed the original sin of being theoretical. And along these lines, I also review how this theorization has been mainly seen in the absolutization of perception when describing the original relationship between human beings and the world. This critical thread, though not explicit, reaches into Husserl’s quarries. Faced with this, secondly, I attempt a possible response to said critique in light of Husserl’s discovery of the absolute flow of consciousness as found in his Lectures on the Internal Time Consciousness.